UJI EFEK ANTIDIARE EKSTRAK ETANOL DAUN MATOA (Pometia pinnata J.R Forst & G. Forst) PADA TIKUS PUTIH JANTAN (Rattus novergicus) - Santi, Irma; Putra, Bayu; Kosman, Rachmat; Ramadhani, Fitrah Anggun; Hativa, Hativa (Fakultas Farmasi UMI, 2023)
Diarrhea is a condition where defecation with a frequency of more than 3 times a day and the consistency of liquid or semi-liquid feces with water content that exceeds normal limits. One plant that is thought to have antidiarrheal effects with tannin content in it is matoa leaves (Pometia pinnata J.R Forst &; G. Forst). This study was conducted experimentally using 25 male white rats induced castor oil (Oleum ricini) as a laxative. After being induced, experimental animals were divided into 5 groups, namely the negative control group (NaCMC), the positive control group (Loperamid), the the ethanol extract of matoa leaves group with doses of 200 mg/KgBB, 400 mg/KgBB, 800 mg/KgBB. All treatments were carried out orally. Then observed the frequency of diarrhea and the consistency of feces every 30 minutes for 5 hours. Furthermore, the results of the study were analyzed statistically using the Kruskal Wallis test then continued with the Post Hoc LSD test. From the results of the study it can be concluded that the ethanol extract of matoa leaves has an antidiarrheal effect on male white rats induced castor oil with an effective dose of 800 mg/KgBB